2009
DOI: 10.1002/jssc.200900036
|View full text |Cite
|
Sign up to set email alerts
|

Reversed phase liquid chromatography trace analysis of pesticides in soil by on‐column sample pumping large volume injection and UV detection

Abstract: The idea of utilization of one hydraulic line of a common commercial HPLC pump for direct on-column sample pumping injection of large sample volumes, 20 mL, was further investigated with the aim to develop multicomponent pesticides trace residues HPLC method in gram soil samples. Target pesticides group involve asulam, atrazine, 2,4-D, PCA, propazine, simazine, 4-chloro-2-methylphenoxyacetic acid, 2-(4-chloro-2-tolyloxy) propionic acid, chlortoluron, metoxuron, epoxiconazole. The results proved the applicabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 43 publications
1
6
0
1
Order By: Relevance
“…The Water Framework Directive (2000/60/EC) established a maximum allowed concentration of 0.1 g L À 1 for each individual pesticide and 0.5 g L À 1 for the sum of pesticides [3]. Therefore, it is necessary to study the distribution of these compounds and the monitoring of trace levels in different environmental matrices because these compounds can produce negative health effects and show negative influence on ecosystems and fauna [4,5]. In this sense, it is necessary to develop reliable, sensitive and efficient techniques for the analysis of trace concentrations of organic pollutants in environmental samples.…”
Section: Introductionmentioning
confidence: 99%
“…The Water Framework Directive (2000/60/EC) established a maximum allowed concentration of 0.1 g L À 1 for each individual pesticide and 0.5 g L À 1 for the sum of pesticides [3]. Therefore, it is necessary to study the distribution of these compounds and the monitoring of trace levels in different environmental matrices because these compounds can produce negative health effects and show negative influence on ecosystems and fauna [4,5]. In this sense, it is necessary to develop reliable, sensitive and efficient techniques for the analysis of trace concentrations of organic pollutants in environmental samples.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, providing clean water and a clean environment for people is the most important matter [1]. Over the last 30 years, synthetic pyrethroids, such as fenvalerate, cyfluthrin, and deltamethrin, have been widely used as agricultural, home insecticides to replace the more toxic and environmentally persistent organochlorine and organophosphorous pesticide.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies also showed that (+)-tebuconazole was accumulated from soil to earthworms with a biota to soil accumulation factor (BASF) of 1.64, whereas (-)-tebuconazole did not accumulate in earthworms [11]. Several studies have focused on the determination of triazoles in soil [12][13][14][15]. Furthermore, a number of technologies, such as high-performance liquid chromatography (HPLC) [16][17][18][19][20], gas chromatography, capillary electrophoresis (CE) [21][22][23], supercritical fluid chromatography (SFC) [24], thin layer chromatography (TLC), simulated moving bed chromatography (SMBC), countercurrent chromatography and microtechnology have been introduced in enantiomers' analysis [25,26].…”
Section: Introductionmentioning
confidence: 99%